1959
DOI: 10.1017/s0016756800059987
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanics of Oblique Slip Faulting

Abstract: SummaryThe various mechanisms which could cause oblique slip faulting are briefly reviewed. It is thought that such faulting may frequently arise from the existence of preferred planes of fracture within the rocks. The dynamics of this mechanism is studied in some detail and an expression is obtained for the first direction of slip within the plane under the influence of a general stress system of given orientation it is found that the initial slip may occur in any possible direction within the plane, the dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
496
0
17

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,054 publications
(516 citation statements)
references
References 3 publications
3
496
0
17
Order By: Relevance
“…Numerical methods for paleostress tensor inversion are based on the assumption that measured striations and shear sense from many individual fault surfaces are a record of a single overall stress tensor responsible for slip on these surfaces. Resolved shear stress orientation on each fault surface is assumed to be parallel to the measured slip vector (Wallace 1951, Bott 1959. Given a large population of individual fault/striae measurements from any single outcrop, ideally with many conjugate sets of faults and some spread in fault orientations, inversion methods allow to search for the overall stress tensor which yields the best fit between theoretically predicted slip direc-Tab.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical methods for paleostress tensor inversion are based on the assumption that measured striations and shear sense from many individual fault surfaces are a record of a single overall stress tensor responsible for slip on these surfaces. Resolved shear stress orientation on each fault surface is assumed to be parallel to the measured slip vector (Wallace 1951, Bott 1959. Given a large population of individual fault/striae measurements from any single outcrop, ideally with many conjugate sets of faults and some spread in fault orientations, inversion methods allow to search for the overall stress tensor which yields the best fit between theoretically predicted slip direc-Tab.…”
Section: Discussionmentioning
confidence: 99%
“…A typ i cal ap proach to the re con struc tion of the palaeostress field is the in verse method, which is based on the as sump tion that the fault move ment is gen er ated in the di rec tion of max imum shear ing stress (Wallace, 1951;Bott, 1959). The in verse prob lem con sists of de ter min ing the mean stress ten sor, knowing the ori en ta tion and sense of slip on nu mer ous faults.…”
Section: Methodsmentioning
confidence: 99%
“…Bott (1959) has shown that the direction of resolved shear stress is determined by the ratio of the principal stress di erences, f,…”
Section: Graphical Construction For the Shear Stress Directionmentioning
confidence: 99%
“…Current attempts to use lineated fault planes as data for palaeostress reconstructions have aroused renewed interest in the theoretical relationship, derived by Wallace (1951) and Bott (1959), between the stress tensor and the direction of maximum resolved shear stress on planes of given orientation. In particular several graphical techniques have been devised for ®nding the shear stress direction (Lisle, 1989;Means, 1989;DePaor, 1990;Ragan, 1990;Fry, 1992;Fleischmann, 1992;Ritz, 1994).…”
Section: Introductionmentioning
confidence: 99%